A scoping review of empirical research on executive functions and game intelligence in soccer - Haugan, J. A.; Lervold, K.; Kaalvik, H.; Moen, F. (Frontiers in Psychology, 2025)
Introduction: Executive functions (EFs)—including working memory, cognitive flexibility, inhibitory control, and planning—are essential for adaptive decision-making in dynamic environments like elite soccer. This scoping review explores the relationship between EFs and game intelligence in adult elite soccer players.